Functional programming of psychophysical events - Prieto Comelin, Arturo (Revista de Psicología, 1998)
Understanding behavior as the interaction between organism and environment involves a reciprocal determinism, where the organism activity is influenced by stimuli conditions and moreover, behavior is generator of environmental events. Traditionally, behavioral research is focused on the stimuli determinism over organism reactions. Therefore, assessing the degree of influence that a stimulus condition exerts over behavior, requires to be obtained from empirical relationships, which permit to differentially infer what proportion of behavioral change has been determined by stimulus conditions. In contrast, focusing on the control exerted by behavior over the environment, it is possible to mathematically program physic stimulus properties according to behavioral dimiensions, which estabalishes an alternative researching method for countless conditioning processes.